The Economic Value of Personal Time: Toward a Grounded Theory - Monray, Jorge (International Journal of Independent Research Studies, 2025)
The concept of time economics has been widely debated in the economic and finance literature, associating these ideas mostly with the dynamics of compound interest rates, opportunity cost theories, or the value of time related to delays in public or private travel time. Nevertheless, the literature has not adequately addressed the measurement of the economic value of time (EVT), considering qualitatively crucial issues such as the age of the individual, financial situation, health, or the perception of the value of free time, among others. This paper presents a mathematical equation that measures in monetary units the real value of “free time” for an individual. This custom-calculated formula integrates six dimensions that are interrelated: opportunity cost, personal financial pressure, age, the family burden factor, the subjective valuation of free time, and perceived health.